2003
DOI: 10.1143/jpsj.72.769
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Wave Description of Haldane-Gap Antiferromagnets

Abstract: Modifying the conventional antiferromagnetic spin-wave theory which is plagued by the difficulty of the zero-field sublattice magnetizations diverging in one dimension, we describe magnetic properties of Haldane-gap antiferromagnets. The modified spin waves, constituting a grand canonical bosonic ensemble so as to recover the sublattice symmetry, not only depict well the ground-state correlations but also give useful information on the finite-temperature properties.PACS numbers: 75.10. Jm, 05.30.Jp, 75.40.Mg … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Here, we use full-diagonalization interacting modified SWT (IMSWT). 49 A conceptually different approach is to introduce Schwinger bosons and treat the resulting Hamiltonian at the mean-field level (Schwinger-boson mean field theory), 50,51 which, however, yields exactly the same excitation spectrum as LMSWT and is hence not further considered here. For the N = 8, s = 5/2 system it was found that a simple correction of the LSWT spectrum, called LSWT + c , gave the best agreement with the exact energies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we use full-diagonalization interacting modified SWT (IMSWT). 49 A conceptually different approach is to introduce Schwinger bosons and treat the resulting Hamiltonian at the mean-field level (Schwinger-boson mean field theory), 50,51 which, however, yields exactly the same excitation spectrum as LMSWT and is hence not further considered here. For the N = 8, s = 5/2 system it was found that a simple correction of the LSWT spectrum, called LSWT + c , gave the best agreement with the exact energies.…”
Section: Discussionmentioning
confidence: 99%
“…For these theories, the ground-state and one-magnon energies can be calculated analytically for AFM wheels. [44][45][46][47][48][49][50][51] The resulting ground-state energies, singlet-triplet gaps, and maximal energies (= heights of the dispersion curves) are listed in Table I, which also presents the corresponding values for the one-J model Hamiltonian obtained from (D)DMRG, see appendix B. Furthermore, the mean deviation of SWT and DDMRG excitation energies or χ 2 = k [ω(k) − ω DDMRG (k)] 2 /( 1 2 NJ s) is given.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, for all these theories, linear SWT (LSWT), interacting SWT (ISWT), linear modified SWT (LMSWT), interacting modified SWT (IMSWT), and SBMFT, analytical results are available for 1D, which can be directly applied to the AFM ring (various IMSWTs exist, we have used the full-diagonalization IMSWT of Ref. 78). Interestingly, the SBMFT yields exactly the same excitation energies as the LMSWT, and also the ground-state energy agree after introduction of a correction factor.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we may consider a bosonic description of ladder systems based on the spin-wave scheme [7]. Since the conventional spin-wave theory is plagued by the difficulty of the zerofield sublattice magnetizations diverging in one dimension, we construct a modified spin-wave theory [8,9] for spin-gapped antiferromagnets.It is along a snake-like path, ði; jÞ ¼ ð1; 1Þ-ð2; 1Þ-ð2; 2Þ-ð1; 2Þ-ð1; 3Þy; that we define spinless fermions. When we introduce renumbered spin operators * S i; j ¼ S i; j ðS % i; j Þ for an odd (even) j; where % i ¼ 3 À i; the spinless fermions are created as c w…”
mentioning
confidence: 99%
“…On the other hand, we may consider a bosonic description of ladder systems based on the spin-wave scheme [7]. Since the conventional spin-wave theory is plagued by the difficulty of the zerofield sublattice magnetizations diverging in one dimension, we construct a modified spin-wave theory [8,9] for spin-gapped antiferromagnets.…”
mentioning
confidence: 99%